(untitled) (CSIAM Transactions on Applied Mathematics, 2020)
Overweight is a social disease, which is transmitted through social networks. A mathematical model is proposed to simulate the dynamics of social obesity, where the structures of individual heterogeneity and overeating behaviors are incorporated. The basic reproduction number of the disease is calculated and is shown to be a threshold for disease invasion. Sufficient conditions for the global stability of an endemic equilibrium is established by Lyapunov functions. Numerical simulations are provided to reveal how interventions through treatment to eating behaviors and education to susceptible individuals suppress the progression of the disease.